21 Performance of growing beef cattle consuming bahiagrass hay treated with calcium oxide and molasses and supplemented with cottonseed meal. (29th July 2019) - Ciriaco, Francine M; Henry, Darren D; Canal, Luara B; Sanford, Carla D; Barreneche, Gonzalo; Luna, Ana C G; Dubeux, Jose C B; DiLorenzo, Nicolas
Abstract: An experiment was conducted to evaluate the effects of bahiagrass (Paspalum notatum) hay treated with calcium oxide (CaO) and molasses, offered ad libitum, on performance of growing beef cattle supplemented with cottonseed meal. Sixty-four growing Bos taurus and Bos indicus influenced heifers (249 ± 26 kg of BW) and steers (249 ± 20 kg of BW) were used in a randomized complete block design. The experiment consisted of a 56 d period in which animals were weighed every 14 d. On d 0, animals were weighed after 16-h water and feed withdrawal, stratified by sex, breed, and BW, and blocked by initial BW. Cattle were then allotted to 16 dormant bahiagrass pastures (1.34 ha each; 4 animals/pasture), which were located in 2 different areas within 0.52 km of each other. Pastures were stratified by location and randomly assigned (n = 8 pastures/treatment) to 1 of 2 treatments: 1) hay treated with 10% molasses (DM basis) + water (to 35% DM; MOL) or 2) hay treated with 5% CaO (DM basis) + 10% molasses (DM basis) + water (to 35% DM; CAO). Cottonseed meal was provided at a rate of 0.3% of cattle BW/d (as fed basis). Data were analyzed using the MIXED procedure of SAS and pasture was the experimental unit. The model included the fixed effects of treatment and sex. Location and block were included as random effects. Initial and final BW were not affected by treatment (P = 0.573, P = 0.453; initial and final BW, respectively) or sex (P = 0.512, P = 0.670; initial and final BW, respectively). Additionally, no effects of treatment (P = 0.767) or sex (P = 0.285) were observed on ADG (average of 0.537 kg). In conclusion, bahiagrass hay treated with molasses alone or in combination with CaO failed to improve performance of growing beef cattle